Taxonomic reconsideration of Lestes dorothea Fraser, 1924, L. decipiens Kirby, 1893, bona species, L. praecellens Lieftinck, 1937 and L. praemorsus Hagen in Selys, 1862 (Odonata, Lestidae) - Hopkins, Paul; Kosterin, Oleg E.; Phan, Quoc Toan; Keetapithchayakul, Tosaphol Saetung (Zootaxa, 2025)
Lestes decipiens Kirby, 1893 is restored in the species rank upon reconsideration of the structure of its male paraprocts against those of L. dorothea Fraser, 1924 and L. praemorsus Hagen in Selys, 1862 s. str. The two latter names could be synonyms. Lestes praecellens Lieftinck, 1937 could be another synonym, which is a matter of further research. The strong differences between the males of L. dorothea and L. decipiens in the male paraprocts are illustrated and the unfortunate confusion concerning this valuable character in literature is discussed. The differences between females of L. dorothea and L. decipiens are outlined. Lestes dorothea is for the first time reported for the fauna of Cambodia, by a finding of the first author in 2024 and re-identification of a specimen in the collection of 2018 by the second author, both from Mondulkiri Province. Its presence also in Laos is inferred from literature. Potentially undescribed Lestes species were recognised in literature reports.